Persepsi Akuntan Pendidik terhadap Overload Standar Akuntansi Keuangan (SAK) bagi Usaha Kecil dan Menengah - Sarita, Buyung; Suhairi, Suhairi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
Financial statement in small and mediums enterprises (SMEs) is low. It is probably resulted by overload of Standar Akuntansi Keuangan (SAK) for SMEs. This paper is preliminary research to analyze the perception of Educational Accountant towards the necessity of SMEs and Large Firms to follow the guidance of SAK in preparing financial statement. Research on 29 respondents found that SAK is overload for SMEs. Further research is suggested to vary and enlarge the number of respondents as for Public Accountant and accountants who work for banks.Keyword: Small and Medium Enterprise, Standar Akuntansi Keuangan, SAK, Overload